Publications of the Identity of Children in Conflict with the Law on the Official Site of the Indonesian Supreme Court Decision Directory - Duflitama Astesa; Cekli Setya Pratiwi (Jurnal Ilmiah Kebijakan Hukum, 2022)
Protection of children's rights in conflict with the law (ABH) is a state obligation. The protection aims to ensure the best interests of the child and to prevent discrimination. As stated in Article 19 of Law Number 11 of 2012, one of the rights is that law enforcement institutions are not allowed to publish the identities of ABH, either in print/ electronic media. However, their identities are still revealed in various Decisions of children's cases. Particularly, their identity is published on the Site of the Supreme Court's Ruling Directory. The purpose of this study is to find out why the Supreme Court Decision Directory Site does not keep the identity of ABH a secret and what are the implications. This research used a socio-legal approach. The results of the study show the management team did not understand their main tasks and rules of protecting the identity of ABH, inconsistency in checking copies of court decisions, ineffective monitoring, and only a handful of people reported the case so this situation is considered normal. The implications of the children's identity disclosure have affected the rights of children, families, and applicable rules that do not provide legal certainty.